Nr CAM is a marker for substrate‐selective activation of ADAM 10 in Alzheimer's disease - Brummer, Tobias; Müller, Stephan A; Pan‐Montojo, Francisco; Yoshida, Fumiaki; Fellgiebel, Andreas; Tomita, Taisuke; Endres, Kristina; Lichtenthaler, Stefan F (EMBO molecular medicine, 2019)
The metalloprotease ADAM10 is a drug target in Alzheimer's disease, where it cleaves the amyloid precursor protein (APP) and lowers amyloid‐beta. Yet, ADAM10 has additional substrates, which may cause mechanism‐based side effects upon therapeutic ADAM10 activation. However, they may also serve—in addition to APP—as biomarkers to monitor ADAM10 activity in patients and to develop APP‐selective ADAM10 activators. Our study demonstrates that one such substrate is the neuronal cell adhesion protein NrCAM. ADAM10 controlled NrCAM surface levels and regulated neurite outgrowth in vitro in an NrCAM‐dependent manner. However, ADAM10 cleavage of NrCAM, in contrast to APP, was not stimulated by the ADAM10 activator acitretin, suggesting that substrate‐selective ADAM10 activation may be feasible. Indeed, a whole proteome analysis of human CSF from a phase II clinical trial showed that acitretin, which enhanced APP cleavage by ADAM10, spared most other ADAM10 substrates in brain, including NrCAM. Taken together, this study demonstrates an NrCAM‐dependent function for ADAM10 in neurite outgrowth and reveals that a substrate‐selective, therapeutic ADAM10 activation is possible and may be monitored with NrCAM.